2012
DOI: 10.1029/2012jb009487
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution size distributions and emission fluxes of trace elements from Masaya volcano, Nicaragua

Abstract: [1] Active volcanoes are significant natural sources of trace elements to the atmosphere yet the processes of emission and the impacts of deposition into terrestrial and aquatic environments remain poorly understood. The varying contributions of volatile degassing and magma ejection (i.e., spattering, spraying, extrusion and fragmentation) to the emission of trace elements from Masaya volcano (Nicaragua) are investigated through measurement of high-resolution trace element size distributions using cascade impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…8b). Such microspheres of 1-20 μm in size were earlier observed in plumes from Kilauea (Meeker and Hinkley, 1993), Masaya (Martin et al, 2009;Moune et al, 2010;Martin et al, 2012), and Villarrica (Sawyer et al, 2011). The most probable source of the microspheres is the bursting of small gas bubbles on the lava surface (Martin et al, 2008).…”
Section: Erta Ale Sublimatesmentioning
confidence: 87%
See 3 more Smart Citations
“…8b). Such microspheres of 1-20 μm in size were earlier observed in plumes from Kilauea (Meeker and Hinkley, 1993), Masaya (Martin et al, 2009;Moune et al, 2010;Martin et al, 2012), and Villarrica (Sawyer et al, 2011). The most probable source of the microspheres is the bursting of small gas bubbles on the lava surface (Martin et al, 2008).…”
Section: Erta Ale Sublimatesmentioning
confidence: 87%
“…In contrast, (1993) recent studies have shown that volatile species of REE can be present in gas in detectable amounts. Some fractionation between LREE and HREE with enrichment of LREE during shallow degassing was observed in aerosol samples from the Masaya volcano (Moune et al, 2010;Martin et al, 2012). Moune et al (2006) argued that HREE were enriched in the eruptive plume of Hekla.…”
Section: Gaseous Transport Of Refractory Elementsmentioning
confidence: 93%
See 2 more Smart Citations
“…6 shows a depletion of volatile elements (Tl, S, Bi, Se, Sb, Cd, Pb, As and B) in mosses compared to the plume. As shown in the previous studies in passive degassing volcanoes, e.g., Erebus, Masaya and Kilauea (Hinkley et al, 1999;Martin et al, 2012b;Mather et al, 2012), these elements are mainly associated with the fine particles that are transported long distances from the source. As a result, only a small percentage of the volatile elements are deposited locally, therefore volcanic emissions have only a minor effect on atmospheric deposition of these elements at the local scale (Calabrese et al, 2011).…”
Section: Geochemical Behaviour Of Elementsmentioning
confidence: 98%